2014
DOI: 10.1161/atvbaha.114.303533
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Phospholipid Transfer Protein on Nascent High-Density Lipoprotein Formation and Remodeling

Abstract: Objective Phospholipid transfer protein (PLTP), which binds phospholipids and facilitates their transfer between lipoproteins in plasma, plays a key role in lipoprotein remodeling but its influence on nascent HDL formation is not known. The effect of PLTP over-expression on apoA-I lipidation by primary mouse hepatocytes was investigated. Approach and Results Over-expression of PLTP through an adenoviral vector markedly affected the amount and size of lipidated apoA-I species that were produced in hepatocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The composition, size and structure of ABCA1-derived nHDL 6,7 as well as the metabolism of nHDL-protein derived from several cell types, including macrophage foam cells, have been reported and are similar. 18,28,29 Cell-ABCA1-derived nHDL is both similar and different from human plasma pre-β HDL. Both contain FC, PL and apo AI.…”
Section: Discussionmentioning
confidence: 99%
“…The composition, size and structure of ABCA1-derived nHDL 6,7 as well as the metabolism of nHDL-protein derived from several cell types, including macrophage foam cells, have been reported and are similar. 18,28,29 Cell-ABCA1-derived nHDL is both similar and different from human plasma pre-β HDL. Both contain FC, PL and apo AI.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that, within the time frame of the HAE assay, lipid-free apoA-I predominantly exchanges onto smaller HDL particles ( 31 ). Furthermore, in vitro studies of HDL remodeling in the absence of apoB particles catalyzed by LCAT ( 42,43 ), PLTP ( 44,45 ), or effl ux capacity included HAE, gender, age, HDL-C, triglycerides, and statin use, and explained over 80% of the J774 effl ux variance, with HDL-C ( b = 0.884, P < 0.0001, 59% model variance explained) and HAE ( b = 0.202, P = 0.031, 26% model variance explained) as the most signifi cant contributors to the model ( Table 3 ). The model for ABCA1-specifi c effl ux capacity explained over 50% of the variance, with HAE as the strongest predictor ( b = 0.342, P = 0.015, 24% explained) followed by HDL-C ( b = 0.390, P = 0.01, 23% explained).…”
Section: Discussionmentioning
confidence: 99%
“…The increased efflux upon SM depletion is due, at least in part, to increased levels of PS in the exofacial leaflet of the PM; this redistribution is due to impaired inward PS translocation upon SM depletion (95). The effect of PL transfer protein (PLTP) is an example of a factor in the extracellular medium that influences ABCA1 activity; PLTP interacts with ABCA1 and stabilizes it (96) thereby promoting ABCA1-mediated FC and PL efflux as well as nascent HDL particle remodeling (97).…”
Section: Factors Influencing Abca1 Activitymentioning
confidence: 99%